The Influence of Customer Relations, Pricing Strategy, and Branding Identity on Customer Satisfaction and Its Impact on Sales Growth PT. ISTA Indonesia - Rahayu Lestari; Christina Evas Joe Likumahua (Budapest International Research and Critics University, 2022)
This study aims to analyze the influence of customer relations, pricing strategy, and branding identity on customer satisfaction and its impact on sales growth. The data of this study used primary data through questionnaires to 100 respondents of PT. Ista Indonesia. Research sampling using purposive sampling. The analysis method used is Partial Least Square (PLS) with the help of the SmartPLS 3.0 application. The results showed that there was a partial influence of branding identity on the customer satisfaction of PT. Ista Indonesia, there is a direct influence of branding identity on the sales growth of PT Ista Indonesia, and there is a direct influence of customer relations on PT. Ista Indonesia's customer satisfaction, there is a direct influence of customer relations on sales growth through customer satisfaction, there is a direct but not significant influence of customer satisfaction on pt. ISTA Indonesia's sales growth. PT. Ista Indonesia, there is a direct influence of pricing strategy but not significantly on the customer satisfaction of PT. Ista Indonesia, there is a direct influence of pricing strategy on the sales growth of PT. Ista Indonesia.